2023
DOI: 10.1371/journal.pgph.0001720
|View full text |Cite
|
Sign up to set email alerts
|

What are the barriers and facilitators to community handwashing with water and soap? A systematic review

Abstract: Handwashing with water and soap (HWWS) is an effective method of cleaning and disinfecting the surface of the hands. HWWS is effective in infection control and prevention transmission, such as in Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). However, rates of handwashing compliance vary globally. This systematic review aimed to identify the barriers and facilitators to community HWWS globally. We conducted a comprehensive search strategy in OVID Medline, OVID Embase, Web of Science Core Collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…These findings corroborate previous reports in which knowledge was associated with hand hygiene practices [ 20 , 26 , 27 ]. A systematic review has also identified knowledge as one of the factors affecting hand washing in the community [ 14 ]. Moreover, having knowledge about COVID-19 has been shown to increase compliance with preventive measures, including hand washing [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings corroborate previous reports in which knowledge was associated with hand hygiene practices [ 20 , 26 , 27 ]. A systematic review has also identified knowledge as one of the factors affecting hand washing in the community [ 14 ]. Moreover, having knowledge about COVID-19 has been shown to increase compliance with preventive measures, including hand washing [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to hand washing depends on complex behavioural considerations, including social and cultural needs and environmental barriers [ 11 13 ]. A recent systematic review cited resource availability, cost and affordability, handwashing station design and infrastructure, accessibility, gender roles, health promotion, time management, knowledge, beliefs and behaviours as factors affecting hand washing in the community [ 14 ]. Low-income countries struggle to provide running water to many of their communities, thus compromising frequent hand washing.…”
Section: Introductionmentioning
confidence: 99%
“…Access to a handwashing station with a functional water tap is one of the main determinants of effective hand hygiene. [29][30][31] Scholars working in low-and middle-income communities found that in infrastructure-restricted communities, in-home handwashing stations improved hand hygiene. 32,33 Our results indicated that the Mini-PASS shifted household handwashing from the washbasin to flowing water.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies showed that the COVID-19 pandemic has increased the use of ABHR, also improving healthcare workers’ compliance with HH [ 9 ]. However, HH remains a longstanding challenge due to concerns linked to the adherences of healthcare workers (HCWs) and the infrastructures and resources needed to focus on its enhancement [ 10 ].…”
Section: Introductionmentioning
confidence: 99%